1981
DOI: 10.1002/bjs.1800681104
|View full text |Cite
|
Sign up to set email alerts
|

Choledochoduodenostomy in calculous biliary tract disease

Abstract: During a 14-year period ending in June 1979, 342 patients with calculous biliary disease underwent choledochoduodenostomy either as a primary procedure or during reoperation. Eighty per cent of the patients were aged 50 years or more. Follow-up was either by personal interview and physical examination or by means of a questionnaire, 90 per cent of the patients being assessed at periods ranging from 6 months to 14 years. A high incidence of common bile duct dilatation was found in older patients, in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Initial resistance to such procedures were based on the presumption of an increase in alkaline gastric reflux and an increase risk of the so-called 'sump syndrome', where vegetable matter is thought to obstruct the anastomosis, predisposing to cholangitis (1,2). However, subsequent reports showed that sump syndrome does not occur (3) or, if it does, occurs only extremely infrequently (4,5) and is actually due to an inadequatesized anastomosis. An additional benefit of the side-to-side anastomosis is that postoperative endoscopic access to the biliary tree is still possible if required.…”
Section: Discussionmentioning
confidence: 99%
“…Initial resistance to such procedures were based on the presumption of an increase in alkaline gastric reflux and an increase risk of the so-called 'sump syndrome', where vegetable matter is thought to obstruct the anastomosis, predisposing to cholangitis (1,2). However, subsequent reports showed that sump syndrome does not occur (3) or, if it does, occurs only extremely infrequently (4,5) and is actually due to an inadequatesized anastomosis. An additional benefit of the side-to-side anastomosis is that postoperative endoscopic access to the biliary tree is still possible if required.…”
Section: Discussionmentioning
confidence: 99%
“…Lygidakis [6] observed the occurrence of postopera tive complications, including incisional hernia, suture problems (stitch abscess or retained unabsorbable suture causing discomfort) and intercostal neuralgic pain in 6.4% of his patients, and reported that no patient devel oped ascending cholangitis or symptoms related to the blind segment. Furukawa et al [9] reported the develop ment of clinical symptoms including pain, fever and jaundice in 33% of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, in many hospitals of Europe and North America, this procedure is carried out as an adjunct to choledocholithotomy, and excellent results have been reported [6,8]. On the other hand, in Japan this operation has also been performed when sim ilar operative procedures were indicated [5,9], But, many people have been critical of this procedure because a blind pouch in the lower region of the choledochus is formed by this operation, and there is a possibility for the occurrence of ascending cholangitis, the sump syn drome, recurrent bile duct stones and pancreatitis [1,3,4], In fact, many investigators, including the authors, have experienced such complications caused by side-toside choledochoduodenostomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations